Use of Lime Suspension and Lime Water as a Solution in Goat Skin Appliance as an Initiative for Implementing Clean Products - Prasetyo Hermawan; Wahyu Fajar Winata (Politeknik ATK Yogyakarta, 2025)
The study aimed to compare the effects of using lime suspension and saturated lime water in the goat skin liming process, focusing on solution properties and skin characteristics. Liming was conducted at 26 °C for 60 minutes using a stirrer, with a skin-to-solution ratio of 1:10 and 2 g Ca(OH)₂ per 100 ml water. The initial pH values were 11.69 (lime suspension) and 11.62 (lime water), while initial conductivity was 7439 μS/cm and 4971 μS/cm, respectively. Observed variables included pH, TDS, electrical conductivity, precipitate weight, and skin weight gain and characteristics. Results showed no significant difference in pH between treatments during liming (p = 0.075) and no significant difference in skin weight gain (p = 0.067). However, solution conductivity differed significantly (p = 0.002), with lime suspension producing higher conductivity values. At the end of liming, precipitate weights were 1.53 g for lime suspension and 0.04 g for lime water, indicating more undissolved material in the suspension method. Skin characteristics, such as color, pH, and elasticity, were similar for both treatments. The findings suggest that while lime suspension and lime water produce comparable results in terms of pH and skin weight gain, they differ in conductivity and precipitate formation. The reduced precipitate in lime water indicates a cleaner process, which could contribute to clean production practices in the leather industry by minimizing solid waste without compromising leather quality. This research provides a scientific basis for considering saturated lime water as an alternative to lime suspension, potentially reducing environmental impact while maintaining product performance in goat skin leather processing.